2006
DOI: 10.1159/000096645
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Behavioral Consequences of Prenatal Fluoxetine

Abstract: Background: Fluoxetine, a selective serotonin reuptake inhibitor, is the most commonly prescribed antidepressant drug for pregnant women. Studies regarding the teratogenic effect of fluoxetine on human and animal models are mainly concerned with structural malformation (congenital anomalies). Aim: Hence, the present study was planned to evaluate the postnatal behavioral effects of fluoxetine on albino rats. Methods: Three groups of female rats received either distilled water or doses of fluoxetine 8 and 12 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
100
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 32 publications
11
100
0
1
Order By: Relevance
“…Alterations in locomotion may be a potential confound in behavioral tests, and false-positives in anxiety-like behavior, for example, may be attributed to altered locomotion. Studies have shown that prenatal fluoxetine exposure increases activity and improves motor coordination in the rotorod test (Bairy et al, 2007). A similar finding was reported with prenatal bupropion exposure (Su et al, 2007).…”
Section: H Behavioral Outcomessupporting
confidence: 65%
See 1 more Smart Citation
“…Alterations in locomotion may be a potential confound in behavioral tests, and false-positives in anxiety-like behavior, for example, may be attributed to altered locomotion. Studies have shown that prenatal fluoxetine exposure increases activity and improves motor coordination in the rotorod test (Bairy et al, 2007). A similar finding was reported with prenatal bupropion exposure (Su et al, 2007).…”
Section: H Behavioral Outcomessupporting
confidence: 65%
“…Several animal studies examined these properties in the context of prenatal SSRI exposure with conflicting results. Impaired weight gain, low birth weight, or small litter size after prenatal SSRI exposure has been reported in several studies (da-Silva et al, 1999;Bairy et al, 2007;Pereira et al, 2007;Cagiano et al, 2008;Favaro et al, 2008;Forcelli and Heinrichs, 2008;Noorlander et al, 2008;Van den Hove et al, 2008;Bauer et al, 2010), whereas other studies observe no differences in weight gain or birth weight (Byrd and Markham, 1994;Stewart et al, 1998;Vartazarmian et al, 2005;Lisboa et al, 2007). Congenital malformations are reported in the clinical literature but have only been reported in the animal literature by extracting and exposing mouse embryos in vitro to 20 times the clinically observed serum concentration of sertraline for 48 hours (Shuey et al, 1992).…”
mentioning
confidence: 99%
“…Bairy et al concluded that prenatal fluoxetine administered to rats caused weight loss and a delay in the transient motor development of fetuses, although it did not, however, compromise postnatal behavior, thus supporting the findings of Speiser et al 21,29 Most studies demonstrate that fluoxetine-treated rats bear low weight offspring. Vartazarmian et al, however, found no weight alterations in fetuses of fluoxetine-treated rats.…”
Section: Discussionmentioning
confidence: 78%
“…20 This study evaluated the possible macroscopic alterations i.e., weight of the fetuses, placentas and encephala and the microscopic alterations i.e., the quantification of frontal lobe nerve cells seen in the fetuses of rats intraperitoneally injected with 10mg/kg/day of fluoxetine and imipramine hydrochloride on the 9 th , 10 th and 11 th day of pregnancy. Fluoxetine was selected for being the antidepressant of choice for pregnant women while 13,21 imipramine was chosen for being a tricyclic antidepressant known to be potentially teratogenic. 22,23 The intraperitoneal route was chosen for being more secure, for providing a faster absorption by the rich blood supply of the large peritoneal area, for not presenting traumatic risks during administration and for constituting a routine laboratory procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The current study shows that it is possible to increase cell proliferation in numerous regions of the postnatal brain in a mouse model for DS. We have used fluoxetine to stimulate neurogenesis, because it is an antidepressant widely used by adults and prescribed in children and adolescents (Boylan et al, 2007) and it has no patent aversive effects on somatic development (Bairy et al, 2007;Einarson et al, 2009). Treatment during the early postnatal period restored neurogenesis and led to the restoration of the total number of neurons in the dentate gyrus.…”
Section: Discussionmentioning
confidence: 99%